The Effect of Reward and Punishment on Employee Performance with Employee Motivation as an Intervening Variable at PT. Bank Rakyat Indonesia (BRI) Regional Office Pekanbaru - Herzoni, Afifah Ramadhani; Marzolina, Marzolina; Rifqi, Ahmad (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the effect of rewards and punishment on employee performance with employee motivation as an intervening variable at PT. Bank Rakyat Indonesia (BRI) Regional Office Pekanbaru. The sampling technique used in this research is probability sampling with a sample size of 115 employees at PT. Bank Rakyat Indonesia (BRI) Regional Office Pekanbaru. The analysis technique used in this research uses the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) using Smart-PLS software version 3.0. The research results show that rewards have a positive and significant effect on employee performance. Punishment has a positive effect and is significant on employee performance. Rewards have a positive and significant effect on employee motivation. Punishment has a positive and significant effect on employee motivation. Motivation is able to mediate the influence of reward and punishment on performance.